1994
DOI: 10.1093/carcin/15.9.2045
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of 1,2-dimethylhydrazine-induced colon tumorigenesis y HMG-CoA reductase inhibitors, pravastatin and simvastatin, in ICR mice

Abstract: 3-Hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors, pravastatin (Pr) and simvastatin (Si), suppressed 1,2-dimethylhydrazine (DMH)-induced colon cancer development in female ICR mice. All mice received an i.p. injection of 10 mg DMH/kg body wt once weekly for 15 weeks. Pr was administered at 0.01, 0.005 and 0.001% levels in drinking water, and Si at 0.01 and 0.002% levels in the diet. All animals had access to Pr or Si throughout the experiments which were terminated at weeks 25 or 30. Histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 0 publications
1
27
0
1
Order By: Relevance
“…Although the effect of pravastatin on the growth of experimental mammary tumors or gastrointestinal tumors in rodents has not been reported, at physiological concentrations, pravastatin does not inhibit the proliferation of human breast cancer cells (50) or gastric carcinoma cells (51) in culture. Interestingly, pravastatin does inhibit the growth of colon tumors in rats (52) and mice (53), in keeping with its ability to inhibit HMG-CoA reductase in intestinal cells (49,54). A reduced risk of colorectal cancer has also been reported in one human trial of pravastatin (16).…”
Section: Fig 4 Mevalonate Increases Cdk-2 Activitymentioning
confidence: 74%
“…Although the effect of pravastatin on the growth of experimental mammary tumors or gastrointestinal tumors in rodents has not been reported, at physiological concentrations, pravastatin does not inhibit the proliferation of human breast cancer cells (50) or gastric carcinoma cells (51) in culture. Interestingly, pravastatin does inhibit the growth of colon tumors in rats (52) and mice (53), in keeping with its ability to inhibit HMG-CoA reductase in intestinal cells (49,54). A reduced risk of colorectal cancer has also been reported in one human trial of pravastatin (16).…”
Section: Fig 4 Mevalonate Increases Cdk-2 Activitymentioning
confidence: 74%
“…Similarly, in our recent study simvastatin administered in the diet at a dose of 180 mg/kg significantly reduced mammary tumor frequency by 80.5% and incidence by 58.5% when compared to controls (Kubatka et al 2011). In 1,2-dimethylhydrazine-induced colon car- cinogenesis in ICR mice, simvastatin and pravastatin significantly reduced tumor frequency (Narisawa et al 1994). Pravastatin has been shown to reduce the incidence and volume of N-nitrosomorpholine-induced rat hepatic neoplastic nodules (Tatsuta et al 1998) and NMU-induced rat colon carcinogenesis (Narisawa et al P. Kubatka et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…32,33 These data further suggest these agents may have a role in cancer prophylaxis as well as therapy. 19,[32][33][34][35] Indeed, recent analyses have demonstrated that inhibitors of HMG-CoA reductase can directly block tumor cell growth both in vitro and in vivo. In this review, we will focus on the antiproliferative activity of the statins, the mechanism of statin-induced apoptosis, and the application of statin therapy as an anti-cancer agent.…”
Section: Figurementioning
confidence: 99%